2015
DOI: 10.1088/1367-2630/18/1/015001
|View full text |Cite
|
Sign up to set email alerts
|

Long-range Ising and Kitaev models: phases, correlations and edge modes

Abstract: We analyze the quantum phases, correlation functions and edge modes for a class of spin-1/2 and fermionic models related to the one-dimensional Ising chain in the presence of a transverse field. These models are the Ising chain with anti-ferromagnetic long-range interactions that decay with distancer as a r 1 , as well as a related class of fermionic Hamiltonians that generalize the Kitaev chain, where both the hopping and pairing terms are long-range and their relative strength can be varied. For these model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

40
258
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 171 publications
(298 citation statements)
references
References 76 publications
40
258
0
Order By: Relevance
“…Independent theoretical works have concluded that LR systems can exhibit many interesting and unusual properties, essentially due to the violation of locality (see e.g. [13][14][15][16][17][18][19][20]). In particular, one-dimensional LR models can host new phases, manifesting striking properties, not present in the SR limit.…”
Section: Pacs Numbersmentioning
confidence: 99%
See 4 more Smart Citations
“…Independent theoretical works have concluded that LR systems can exhibit many interesting and unusual properties, essentially due to the violation of locality (see e.g. [13][14][15][16][17][18][19][20]). In particular, one-dimensional LR models can host new phases, manifesting striking properties, not present in the SR limit.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…In particular, one-dimensional LR models can host new phases, manifesting striking properties, not present in the SR limit. [15][16][17][21][22][23][24][25][26][27][28][29][30].…”
Section: Pacs Numbersmentioning
confidence: 99%
See 3 more Smart Citations